2009
DOI: 10.1139/f09-132
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in probabilistic maturation reaction norms and growth of Atlantic cod (Gadus morhua) on the Icelandic shelf

Abstract: Decreasing temporal trends in probabilistic maturation reaction norm (PMRN) midpoints, symptomatic of earlier maturation despite environmentally induced variation in growth, have been observed in many exploited fish stocks. Here, we studied the growth and maturation trends of female and male Icelandic cod ( Gadus morhua ) by estimating PMRN midpoints for cohorts 1964–1999 and found evidence that a shift towards maturation at smaller sizes and younger ages has occurred independently of changes in growth, condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 74 publications
(110 reference statements)
2
20
1
Order By: Relevance
“…Model Description), lending good empirical support to this model and providing evidence for more strongly density-dependent growth. However, aquaculture studies of Atlantic cod (62,63) suggest a high genetic variance in growth, and previous studies of other species found evidence for harvest-induced evolution of growth (10,29,64,65), suggesting that weaker density dependence and more evolution of growth are possible. Another possibility is that the strength of density-dependent growth has varied over time, which could happen if, for example, ecosystem conditions have changed (66,67).…”
Section: Discussionmentioning
confidence: 88%
“…Model Description), lending good empirical support to this model and providing evidence for more strongly density-dependent growth. However, aquaculture studies of Atlantic cod (62,63) suggest a high genetic variance in growth, and previous studies of other species found evidence for harvest-induced evolution of growth (10,29,64,65), suggesting that weaker density dependence and more evolution of growth are possible. Another possibility is that the strength of density-dependent growth has varied over time, which could happen if, for example, ecosystem conditions have changed (66,67).…”
Section: Discussionmentioning
confidence: 88%
“…The selection represents our best knowledge about relevant studies, but probably many studies have been missed, particularly when results were inconclusive or negative and not reported among the main results. There are seven studies of marine fish species that have all found positive evidence, but in all but two (Pardoe et al 2009, Swain et al 2008) changes in growth are attributed to changes in maturation. Studies on freshwater or anadromous species have covered 13 species, mostly salmonids.…”
Section: Life-history Traitsmentioning
confidence: 99%
“…Since cod, female whiting and haddock PMRNs have varied, demography and growth-dependent plasticity cannot fully explain temporal changes in their maturity ogives: changes in maturation propensity due to growth-independent plasticity in response to environmental conditions and/or fisheries-induced evolution in maturation are likely to have also played a role. Negative temporal trends in PMRN midpoints have already been observed for inshore haddock along the Scottish coast (Wright et al 2011a, but see Devine & Heino 2011) as well as for other cod stocks (Heino et al 2002b, Olsen et al 2004, 2005, Yoneda & Wright 2004, Pardoe et al 2009 Table 2. Regression coefficients and their standard errors (SE) for cod L p50 at age 3, haddock L p50 at age 2 and whiting L p50 at age 2, obtained from transforming back to the original set of axes the principal component regression coefficients and their SEs.…”
Section: Temporal Trends In Pmrnsmentioning
confidence: 91%
“…Gadid stocks have been shown to be prone to fisheries-induced changes in their life history (Jørgensen 1990, Olsen et al 2004, Pardoe et al 2009, Devine & Heino 2011, Wright et al 2011a. North Sea gadids therefore provide an adequate study system for a comparative analysis of fisheries-induced changes in maturation.…”
Section: Introductionmentioning
confidence: 99%